AICCRA report: Technical Working Group and Staff Induction Meeting on Participatory Rangeland Management - Mukalo, Irene Aloo; Mohamed, Said (International Livestock Research Institute, 2023)
This report provides a comprehensive summary of the Technical Working Group (TWG) and Staff Induction Meeting on Participatory Rangeland Management (PRM) held on the 23rd and 24th of August 2023 at the Wajir Palace Hotel in Wajir County. The meeting was conducted as part of the AICCRA project, Kenya in partnership with the International Livestock Institute (ILRI). The primary goal of this initiative is to promote climate-smart pastoralism practices in arid and semi-arid (ASAL) regions of Kenya. To achieve this objective, ILRI has partnered with the Resource Conflict Institute (RECONCILE) to implement the participatory rangeland management approach in the Arbahajan Ward of Wajir County.